Enduring shame : a recent history of unwed pregnancy and righteous reproduction - Adams, Heather Brook (University of South Carolina Press, 2022)
"It was not long ago that unmarried pregnant women in the US hid in maternity homes and relinquished their "illegitimate" child to a more "deserving" two-parent family-all in the name of keeping secret a shameful pregnancy. While times and practices have changed, reproductive politics remains a fraught topic and site of injustice, lingering sexual shame contributing to racialized and class-based public division. Enduring Shame explores two volatile decades in US history-the 1960s and the 1970s-to trace how shame remained a dynamic and animating emotion in increasingly public ways of addressing "unwed" and "teen" pregnancy. Heather Brook Adams makes a case for recasting this era not as a time of gaining reproductive rights for all, but rather as a moment when communicative practices of shame and blame cultivated new forms of injustice. Drawing from personal interviews, archival documents, legal decisions, public policy, journalism, memoirs, and advocacy writing, Adams articulates the rhetorical power of shame to explain how the American public was persuaded to think about reproduction, sexual righteousness, and unwed pregnancy during a time of codified "progress." Despite the aspirational goals of reproductive liberation, public sentiment frequently upheld supremacist notions of whiteness that were based on ideas of racial, economic, and moral fitness-even as these sentiments informed new public policy. By centering evidence of shame as a communicated or threatening force, the book maps a range of experiences across these decades from women's experiences of hiding and "revirginalization" in homes for unwed mothers to policy and legal changes that are typically understood as proof of shame's dissipation. Adams explores evidence related to Title IX legislation, Roe v. Wade, and the unrelenting Hyde Amendment that has long restricted reproductive autonomy for poor (often non-white) women, and Congressional interventions of the late 1970s meant to curb an "epidemic" of "babies having babies." Rhetorical historiography and questions of reproductive justice guide the analysis and women's own voices provide essential perspectives and context for this recent history. This book recovers a misunderstood part of women's recent history by considering why reproductive politics remain so volatile given women's previous gains in this area and why shame continues to figure so centrally and powerfully in public discourse about limitations on women's reproductive and sexual freedoms"--